Metric handbook planning and design data - David, 1932- (Oxford, England : Architectural Press, 2008)
Design data for architects and building designers to use with various programs.
System requirements: PC; Windows 95 or 98 or Windows NT 4.x; 4MB free space (software only) or 150MB (full installation); CAD software package.
Keywords: Building -- Details -- Drawings; Metric system; Drawings